Identification and analysis of immunological activity of two isoforms of tropomyosin in Alectryonella plicatula - Shiqiang Yang; Yexin Chen; Fei Huan; Xinrong He; Xiao Yun; Hong Liu; Guixia Chen; Guangming Liu (Food Science and Human Wellness)
Oyster, as a common aquatic food, play an important role in shellfish allergy. In this study, 2 tropomyosin (TM) isoforms TM-α and TM-β (TM-α/-β) in Alectryonella plicatula were identified. The sequences of 852 bp encoding 284 amino acids of TM-α/-β and 2 recombinant proteins were obtained, respectively. There were 12 amino acid differences between TM-α/-β. The results of immunological experiments indicated that TM-β had stronger immunobinding activity and immunoreactivity than those of TM-α. Structural analysis showed that TM-β had more α-helix and higher surface hydrophobicity than TM-α. Sequences and epitopes alignment with shellfish TMs revealed that amino acids of TM-β were more frequently recognized as IgE epitopes in other shellfish TMs than TM-α. Differences in structure and sequence account for the higher immunological activity of TM-β compared to TM-α. These findings provide a theoretical basis for enriching the understanding of shellfish TM and accurate diagnosis of allergic components.